A test of the cosmogenic 10Be(meteoric)/9Be proxy for simultaneously determining basin‐wide erosion rates, denudation rates, and the degree of weathering in the Amazon basin. Issue 12 (14th December 2015) - Wittmann, H.; von Blanckenburg, F.; Dannhaus, N.; Bouchez, J.; Gaillardet, J.; Guyot, J. L.; Maurice, L.; Roig, H.; Filizola, N.; Christl, M.
Abstract: We present an extensive investigation of a new erosion and weathering proxy derived from the 10 Be(meteoric)/ 9 Be(stable) ratio in the Amazon River basin. This new proxy combines a radioactive atmospheric flux tracer, meteoric cosmogenic 10 Be, with 9 Be, a trace metal released by weathering. Results show that meteoric 10 Be concentrations ([ 10 Be]) and 10 Be/ 9 Be ratios increase by >30% from the Andes to the lowlands. We can calculate floodplain transfer times of 2–30 kyr from this increase. Intriguingly however, the riverine exported flux of meteoric 10 Be shows a deficit with respect to the atmospheric depositional 10 Be flux. Most likely, the actual area from which the 10 Be flux is being delivered into the mainstream is smaller than the basin‐wide one. Despite this imbalance, denudation rates calculated from 10 Be/ 9 Be ratios from bed load, suspended sediment, and water samples from Amazon Rivers agree within a factor of 2 with published in situ 10 Be denudation rates. Erosion rates calculated from meteoric [ 10 Be], measured from depth‐integrated suspended sediment samples, agree with denudation rates, suggesting that grain size‐induced variations in [ 10 Be] are minimized when using such sampling material instead of bed load. In addition, the agreement between erosion and denudation rates implies minor chemical weathering intensity in most Amazon tributaries. Indeed, the Be‐specific weathering intensity, calculated from mobilized 9 Be comprising reactive and dissolved fractions that are released during weathering, is constant at approximately 40% of the total denudation from the Andes across the lowlands to the Amazon mouth. Therefore, weathering in the Amazon floodplain is not detected. Key Points: 10 Be/ 9 Be ratios in sediment and river water provide weathering and erosion rates in the Amazon Meteoric denudation rates agree within a factor of 2 with published in situ rates Basin‐wide Be weathering intensity is approximately 40% with no floodplain weathering resolvable